2004
DOI: 10.1021/bi0490284
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Mechanism of Blebbistatin Inhibition of Nonmuscle Myosin IIB

Abstract: We examined the effect of blebbistatin on the kinetic properties of nonmuscle myosin IIB subfragment 1 (NMIIB S1). Blebbistatin is a small molecule that affects cell blebbing during the process of cell division, which has been shown to decrease the myosin ATPase activity of a number of myosins [Straight et al. (2003) Science 299, 1743-1747]. The steady-state actin-activated ATPase activity of NMIIB S1 was decreased approximately 90% at 40 microM actin in the presence of blebbistatin. Stopped-flow techniques we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
81
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 18 publications
10
81
0
Order By: Relevance
“…1B). These results are consistent with blebbistatin binding to the myosin-ADP-Pi complex, inhibiting the rate of release of P i and trapping myosin in an F-actin weak-binding state, as has been proposed from more detailed studies of skeletal muscle myosin II (25) and nonmuscle myosin IIB (26).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…1B). These results are consistent with blebbistatin binding to the myosin-ADP-Pi complex, inhibiting the rate of release of P i and trapping myosin in an F-actin weak-binding state, as has been proposed from more detailed studies of skeletal muscle myosin II (25) and nonmuscle myosin IIB (26).…”
Section: Resultssupporting
confidence: 88%
“…1A). As was reported for skeletal muscle myosin II (25) and nonmuscle myosin IIB (26), blebbistatin also inhibits the basal (non-actin-activated) MgATPase of Dictyostelium myosin II (Fig. 1 A), with a slightly lower IC 50 .…”
Section: Resultssupporting
confidence: 81%
“…During the myosin ATPase cycle, this cleft characteristically closes as a result of structural rearrangements in the nucleotide-binding site mediating the process of Pi release and subsequent ADP release [28]. Blebbistatin binding stabilizes the closed ADP/Pi bound myosin II intermediate state, thus preventing the release of Pi and the associated myosin power stroke (i.e., the force generating step) ( Figure 1) [27,29,30]. Blebbistatin is highly suited for studies of the cellular functions of cytoplasmic myosin II, as it blocks myosin II activity in an actin-detached state, thus, preventing artifacts from the formation of strongly bound nonfunctional actomyosin complexes [29].…”
mentioning
confidence: 99%
“…However, a series of functional, kinetic and structural investigations have shown that (S)-(-)-blebbistatin (1) achieves selectivity by binding in a highly hydrophobic cleft in the myosin motor domain. [5][6][7][8] Surprisingly, this is one of the most conserved components of all myosin motor domains where a few small sequence and structural differences lead to the ability of 1 to discriminate between myosin isoforms.…”
Section: Introductionmentioning
confidence: 99%